Evaluasi Tingkat Kebisingan Di PT PLN (Persero) Unit PLTD/G Teluk Lembu - Hesti Mulyani; Aryo Sasmita; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
PT PLN (Persero) Unit PLTD/G Teluk Lembu in its operational activities potentially able to evoke noise from generator machines. The employees that are frequently exposed to the noise can affect the employees’ health and comfort. The purpose of this research is to determine the noise’s intensity from the generator machines, the length of exposure time, and the mapping of noise spread pattern. The noise measurement method is based on KepMenLH No 48 Tahun 1996, and the device that is used is Sound Level Meter (SLM). The measurement of sound pressure level (Leq) took place for 1 day. Based on the data processing result from 13 measurement spots, there are 9 spots that exceed the quality standards based on KepmenLH No. 48 Tahun 1996. The highest loudness level is 104,17 dB where this spot located very close from the noise source, and the lowest loudness level is on 74,41 dB where the distance is quite far from the noise source. The planned noise control attempt is by using noise barrier (naturally or artificially), isolate the machines, machine care, the administration management, and the human resource management.Keyword: Loudness, noise, PLTD/G